Hubungan Antara Regulasi Diri Dalam Belajar dengan Kematangan Karier Pada Peserta Didik Kelas XI-XII SMAKr Pandhega Jaya Kupang - Vinsenso Tabelak; Yeni Damayanti; Mernon Yerlinda Chalista Mage (Fakultas Psikologi Universitas Kristen Satya Wacana, 2024)
This study aims to examine the relationship between self-regulation in learning and career maturity among 11th-12th grade students at SMA Kristen Pandhega Jaya. Self-regulation in learning encompasses the ability to plan, monitor, and evaluate learning activities independently, while career maturity involves the readiness to make mature career decisions. This research used a correlational quantitative method with a sample of 58 students. Data were collected through questionnaires measuring self-regulation in learning and career maturity scales, and analyzed using the Pearson correlation technique. The results showed a significant positive relationship between self-regulation in learning and career maturity (r = 0.543, p < 0.05), indicating that students with good self-regulation tend to have higher career maturity. The implications of this study emphasize the importance of developing self-regulation in learning programs to support students' career maturity. Keywords: self-regulation in learning, career maturity, high school students, correlation